Predicting Academic Achievement and Attainment: The Contribution of Early Academic Skills, Attention Difficulties, and Social Competence. Issue 2 (1st June 2016) - Rabiner, David L.; Godwin, Jennifer; Dodge, Kenneth A.
Abstract: Research predicting academic achievement from early academic, attention, and socioemotional skills has largely focused on elementary school outcomes and rarely included peer assessments of social competence. We examined associations between these early child characteristics and academic outcomes into young adulthood using the Fast Track normative sample ( n = 386). Reading achievement after fifth grade was significantly higher in children with better early reading skills and significantly lower in children with early attention difficulties. Math achievement was predicted by early reading and math skills, while school grades were significantly lower in children with lower peer acceptance and higher attention difficulties. Children with early attention difficulties were 40% less likely to graduate from high school. Years of education by young adulthood was significantly reduced in children with lower early reading skills, lower social acceptance, and higher attention difficulties; these early child characteristics affected long-term academic outcomes indirectly through their impact on intermediate academic outcomes.